Dimensión del cuidado de enfermería a los colectivos : un espacio para la promoción de la salud y la producción de conocimiento (1999)
ABSTRACT: In this article, some ideas about the dimension of nursing care to collectives, its human and social nature and its importance as a space for the promotion of health and the production of integral knowledge are proposed. The methodology of this study includes the articulation of a quantitative methodology of an empirical-analytical model as well as a qualitative methodology of historical-hermeneutic and critical-social models. The meaning of being healthy or sick for the human collectives, and the meaning of their daily practices enriches and depends the understanding of the collective health and disease process in order to change it together. This change happens by playing an autonomous and participative role of collectives in order to educate the community within the process of individual and collective identity. In this process, human development, which is the basis of life and health promotion is proposed.